Aktualisasi Nilai-Nilai AjaranIslam Melalui Budaya Sekolah Di SMP Plus Darus Sholah Jember - Nur Agustin, Diyah Ayu (IJIT: Indonesian Journal of Islamic Teaching, 2020)
Islam is a religion of rahmatan lil alamin, which means a religion that brings mercy to humans and the universe. Islam is believed by its adherents to be a religion that has universal values ​​and teachings, which are presented as basic principles for Muslims in their lives and to respond to the realities of life. Islamic teachings have basic foundations that are used as references and guidelines by all mankind. Islamic teachings include aqidah, shari'ah and morals. The school as an educational institution that wants to equip its students to become an institution of control over the moral and social development of society and is able to manifest Islamic character, character and ethics. A good school culture will give birth to a good ecosystem as well. The importance of actualizing Islamic teachings through school culture is expected to make students better in practicing or applying these values ​​both at school and in everyday life outside school.